The Influence of Sales Competency on Sales Performance and Revenue Growth: The Mediating Role of Work Motivation (Evidence from Sales Personnel at CV Sinar Maju Distributor Keramik IKAD) - Purba, Mambang Purwanto (Universitas Mohammad Husni Thamrin, 2026)
This study aims to analyze the effect of sales competence on performance and sales improvement with work motivation as a mediating variable among sales personnel at CV Sinar Maju, a distributor of IKAD ceramic tiles. The research subjects are sales personnel with more than one year of work experience. A quantitative approach was employed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that: (1) sales competence has a positive and significant effect on performance and sales improvement; (2) sales competence has a positive and significant effect on work motivation; (3) work motivation has a positive and significant effect on performance and sales improvement; and (4) work motivation mediates the effect of sales competence on performance and sales improvement. These findings underscore the importance of developing sales competence integrated with work motivation enhancement programs to improve sales performance in building materials distribution companies.